ANALISIS INTEGRASI BURSA EFEK JAKARTA DENGAN PASAR MODAL DUNIA : Menggunakan Uji Akar-akar Unit - Muharam, Harjum (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2001)
Increasing of Capital Market in Indonesia Become interesting topic to be analysed. Capital market integration is one part of the topic that challenges to be researched. Economic crisis in Indonesia gives big impact on Indonesian Capital Market. In order to anticipate more impact of the crisis, in September 1997 Indonesian Government Liberated foreign ownership limit for stock at Jakarta Stock Exchange. Theoresically this liberated make JSX integrated to World Capital Market and the movement of HISG has positive correlation with international indexes. To know the real condition is the reason why this JSX and World Capital Market. Bivariate cointegration test between HISG and each indexes results ADF observed valu bigger than ADF table value for all cases at alfa 5% and 10%. This result has means that HISG has cointegreted with the the indexes and proofs the hypothesis of integration between JSX and World Capital Market is true.